Peran TNI dalam Pembinaan Teritorial (Studi Kasus di Desa Sungai Ceper, Kecamatan Sungai Menang, Kabupaten Ogan Komering Ilir, Sumatera Selatan) - Santi, Tri Kusuma (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
The title of this research is "The Role of The Indonesian Militer In The Development of The Territorial (Case Study in Sungai Ceper Village, Sungai Menang District, Ogan Komering Ilir District)". TNI in the context of defending territory, assisting the tasks of regional governments based on Law Number 34 of 2004 concerning the TNI in the development of physical or non-physical communities, territorial development, community empowerment in territorial / remote / remote areas and improving the welfare of the community through TNI Manunggal Building Village (TMMD) program. The purpose of this research is to find out how the relationship between military and civilian is formed through the TNI Manunggal Building Village (TMMD) program and the implementation of the TNI Manunggal Building Village activities when viewed from a human security approach. The method used in this study is a qualitative approach with stages, namely interviews, observation, documentation. Meanwhile, the source of this research is primary data sources. Based on the results of the study it can be seen that, physical achievements in the implementation of the TNI Manunggal Building Villages have been carried out based on the target, but there is one thing that makes constraints in achieving these targets. Then, the relationship between the military and civilians was well established because through the TNI Manunggal Building Village program, and the closer cooperation between the TNI and the Government. Then, through this activity the target area community is able to obtain aspects of the human security approach in the form of personal security.